Pediatric Cardiac ECMO: A review - Gaurang Upadhyay; Suresh Rao; Vinay Joshi; Preetha Joshi (Wolters Kluwer Medknow Publications, 2017)
Patient with congenital or acquired heart disease comprise a major diagnostic category for Pediatric intensive care units across the country, comprising of 30-40% more admission to some of the centres. Over the last 10 years, there has been a dramatic increase in the use of extracorporeal membrane oxygenation (ECMO) in cardiac failure despite absence of encouraging survival statistics. ECMO can be a useful tool in our country in patients who undergo open heart surgery and are in refractory low cardiac output, if instituted electively before a cardiac arrest. Veno-arterial extracorporeal membrane oxygenation (V-A ECMO) is a common modality of circulatory assist used presently in children in our country. This mode can also be used as bridge to heart transplant. This review addresses the following issues for Pediatric Cardiac ECMO: indications and contraindications of VA ECMO, complications, basic ECMO circuit, routine management and management in special circumstances, along with troubleshooting and long term neurological outcome and survival.